In Vitro Antihelmintic Effect of Mahagoni (Swietenia mahagoni Jacq) Seeds Etanol ExtractAgainst Ascaris suum Goeze - Yusuf Arif Salam; Yulia Sari; Sigit Setyawan (Nexus Biomedika, 2017)
Introduction: Mahagoni seeds contain flavonoid, saponin, and tannin that that have been known having anthelmintic effect. This study aimed to determine the antihelmintic effect of mahagoni (Swietenia mahagoni Jacq) seeds etanol extract against Ascaris suum Goeze in vitro. Methods:The study was a laboratory experimental research using post test only controlled group design. The subject were adult Ascaris suum Goeze worms. The sampling technique used was quota sampling. This research was using mahagoni (Swietenia mahagoni Jazq) seeds etanol extractwith concentration 30% w/v, 50% w/v, 70% w/v, 90% w/v, NaCl 0.9% (negative control), and albendazol 0.5% (positive control).Data were analyzed with Pearson correlation test to determine correlation between concentration of mahagoni (Swietenia mahagoni Jacq) seeds etanol extract and amount of worms death. Probit analysis has been done to find LC50. Results: Pearson correlation test showed significant result p=0.00 and strong correlation r = 0.87. Probit analysis results showed LC50mahagoni (Swietenia mahagoni Jacq) seeds etanol extract was 40.66% w/v. It means that 40,66% concentration of mahagoni (Swietenia mahagoni Jacq) seeds etanol extract can cause the death of half sample. Conclusions:Mahagoni(Swietenia mahagoni Jacq) seeds etanol extract had effects to the mortality of Ascaris suum Goeze in vitro with strong correlation between additional amount of extract concentration and amount of worms with LC50value= 40,66% w/v. Keywords :Antihelminthic, Swietenia mahagoni Jacq, alkaloid, Ascaris suum Goeze